A study of risk factors of retinopathy of prematurity in a tertiary care hospital - Dr. Shivananda I; Dr. Srinivasa V; Dr. Kumar G.V.; Dr. Vijay Yadav (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Retinopathy of prematurity (ROP) is a vaso-proliferative disorder of the retina, which principally occurs in premature neonates during vascular development and maturation stage. ROP is multifactorial disorder. Objectives: The purpose of this study is to know the risk factors and their correlation with retinopathy of prematurity. Methods: All neonates born between 28-34 weeks of gestation admitted in NICU, who are under oxygen, were included in the study and screened for ROP. Babies with ocular disorder which interfere with fundus examination and babies who did not complete follow up till complete vascularization of retina were excluded from the study. Results: A total of 95 neonates were studied for ROP. In babies with gestational age between 30 – 32 weeks, 15.4%, 8.5% in the 32 – 35 weeks and none among those born between more than 35 weeks had ROP. About 12.5% of the patients with no PDA and 57.1% of the patients with PDA had retinopathy of prematurity. About 10.8% of the patients with no anemia and 33.3% with anemia had retinopathy of prematurity. This study had shown that 9.6% of the patients without blood transfusion and 36.4% with blood transfusion had retinopathy of prematurity. In this study 10% of the newborns with no thrombocytopenia and 32% with thrombocytopenia had retinopathy of prematurity.Retinopathy is an important complication of prematurity. Conclusion: Timely referral of detected ROP cases for treatment prevents blindness. There is need for the obstetricians, neonatologist and ophthalmologist to work in close co-operation to prevent blindness due to ROP.